Restricted epitope specificity determined by variable region germline segment pairing in rodent antibody repertoires. Issue 1 (1st January 2020) - Hsiao, Yi-Chun; Chen, Ying-Jiun J.; Goldstein, Leonard D.; Wu, Jia; Lin, Zhonghua; Schneider, Kellen; Chaudhuri, Subhra; Antony, Aju; Bajaj Pahuja, Kanika; Modrusan, Zora; Seshasayee, Dhaya; Seshagiri, Somasekar; et al.
ABSTRACT: Antibodies from B-cell clonal lineages share sequence and structural properties as well as epitope specificity. Clonally unrelated antibodies can similarly share sequence and specificity properties and are said to be convergent. Convergent antibody responses against several antigens have been described in humans and mice and include different classes of shared sequence features. In particular, some antigens and epitopes can induce convergent responses of clonally unrelated antibodies with restricted heavy (VH ) and light (VL ) chain variable region germline segment usage without similarity in the heavy chain third complementarity-determining region (CDR H3), a critical specificity determinant. Whether these V germline segment-restricted responses reflect a general epitope specificity restriction of antibodies with shared VH /VL pairing is not known. Here, we investigated this question by determining patterns of antigen binding competition between clonally unrelated antigen-specific rat antibodies from paired-chain deep sequencing datasets selected based solely on VH /VL pairing. We found that antibodies with shared VH /VL germline segment pairings but divergent CDR H3 sequences almost invariably have restricted epitope specificity indicated by shared binding competition patterns. This epitope restriction included 82 of 85 clonally unrelated antibodies with 13 different VH /VL pairings binding in 8 epitope groups in 2 antigens. The corollary that antibodies with shared VH /VL pairing and epitope-restricted binding can accommodate widely divergent CDR H3 sequences was confirmed by in vitro selection of variants of anti-human epidermal growth factor receptor 2 antibodies known to mediate critical antigen interactions through CDR H3. Our results show that restricted epitope specificity determined by VH /VL germline segment pairing is a general property of rodent antigen-specific antibodies.